Pembuatan Papan Nama Dan Sign System UMKM Dapoer Mini Di Kelurahan Gunung Anyar - Dava Praya Syafa Kurniawan; Antonius Dian Kurnianto; Elvira Dewanti Libragiantari (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Nameplates, also known as nameplates, are small signs or boards usually made of materials such as metal, wood, plastic, or acrylic that identify a particular place. While Sign System is a system or series of signs used to provide information to people in a certain environment. Therefore, Nameplates and Sign Systems are needed by MSMEs as the owner's identity, one of which is Dapoer Mini in Gunung Anyar Village. So, KKN activities were carried out by Group 87 to make these two things. Using the method of carrying out observation, analysis, making nameplates and sign systems, and installing them. It is hoped that the existence of a signboard and sign system can help provide information to buyers who want to buy products at MSMEs Dapoer Mini.